Gender and grace love, work & parenting in a changing world - Van Leeuwen, Mary Stewart 1943- (Downers Grove, IL IVP, 1990)
Includes bibliographical references and index.
Keywords: Sex role -- religious aspects -- Christianity; Parenting -- religious aspects -- Christianity